Comparing different assessments of remnant lipoprotein cholesterol: The very large database of lipids - Faridi, Kamil F.; Quispe, Renato; Martin, Seth S.; Hendrani, Aditya D.; Joshi, Parag H.; Brinton, Eliot A.; Cruz, Daniel E.; Banach, Maciej; Toth, Peter P.; Kulkarni, Krishnaji; Jones, Steven R. (Journal of clinical lipidology, 2019)
Remnant lipoprotein cholesterol (RLP-C) is a risk factor for atherosclerotic cardiovascular disease, but there is no standard method for measurement. Some studies have used very low-density lipoprotein cholesterol estimated by the Friedewald equation to approximate RLP-C using a basic lipid panel, whereas others have attempted to measure RLP-C with ultracentrifugation. The aim of the study was to compare RLP-C levels estimated from basic lipid parameters to those measured by ultracentrifugation. We analyzed 1,350,908 individuals from the Very Large Database of Lipids, comparing one estimate of RLP-C using basic lipid parameters (RLP-Cestimated = non–high-density lipoprotein cholesterol − Friedewald-estimated low-density lipoprotein cholesterol for triglycerides <355 mg/dL [4 mmol/L], or non–high-density lipoprotein − directly measured low-density lipoprotein for triglycerides ≥355 mg/dL) to levels measured by vertical auto profile ultracentrifugation (RLP-Cmeasured = dense subfraction of very low-density lipoprotein cholesterol + intermediate-density lipoprotein cholesterol). We calculated correlations between RLP-Cestimated and RLP-Cmeasured along with median within-subject differences between RLP-Cestimated and RLP-Cmeasured across quintiles of RLP-Cestimated. We also assessed correlations with RLP-C estimated from basic lipid parameters using a novel method of calculating low-density lipoprotein cholesterol with a patient-specific conversion factor (RLP-Cestimated-N). Our cohort was 48% male, and median (interquartile range) age was 59 (49–69) years. Median (interquartile range) RLP-Cestimated and RLP-Cmeasured were 23 (16.4–33.2) and 24 (19–32) mg/dL, respectively. The correlation between RLP-Cestimated and RLP-Cmeasured was 0.76. Based on the specified definition of RLP-Cestimated, the correlation between RLP-Cestimated and triglyceride/5 for triglyceride < 355 mg/dL was exactly 1.0. RLP-Cestimated was lower than RLP-Cmeasured in the first and second quintiles of RLP-Cestimated but greater in the highest quintile. The correlations with RLP-Cestimated-N were 0.98 and 0.81 for RLP-Cestimated and RLP-Cmeasured, respectively. A previously used estimate of RLP-C using basic lipid parameters correlates weakly with remnants measured by ultracentrifugation. Our findings emphasize the need to standardize definitions and measurements of RLP-C. •Remnant lipoproteins are a risk factor for atherosclerotic cardiovascular disease.•A consensus method for measuring remnant lipoproteins is lacking.•Two previously studied assessments of remnant lipoproteins are weakly correlated.•Measured correlations are weaker at higher levels of remnant lipoproteins.•A standardized measurement of remnant lipoproteins is still needed.